Deposition of sprayed drops in soybean in function of sowing spacing - Viegas Neto, Antonio Luiz; Souza, Cristiano Márcio Alves de; Degrande, Paulo Eduardo; Lima Júnior, Izidro dos Santos (Scientia Agraria Paranaensis, 2021)
To reach all parts of the plants can be a difficult achievement faced by the drops in several crops. Strategies in crop management such as an increment in the plant spacing can contribute to the spray application’s success. This study aimed to evaluate the droplets deposition in soybean, using three different spray nozzles and application rate, in two soybean rows spacing. The experimental design used was the randomized blocks, with treatments arranged in a split-plot scheme. The plots were the interrow spacing (0.45 and 0.76 m), the subplots were the spray nozzles (JA-2 and Magno 11002 BD), and the sub-subplots were the application rate (120, 200 and 280 L ha-1). Droplets coverage was evaluated in the upper, middle and lower thirds of soybean plants. Water-sensitive papers were installed in the adaxial part of plant leaves to analyze the spray technology and evaluated using E-Sprinkle® software. Spraying was performed in plants at the R5.3 soybean stage. This experiment evaluated the following parameters: the volume median diameter, the density of droplets per cm2, the droplet coverage area, and the droplet percentage less than 150 µm. The increase in the soybean row spacing combined with the spray volume increase provided greater droplet coverage in the middle third in soybean crop. The Magno 11002 BD droplet nozzle provided the higher droplet coverage in the row spacing of 0.76 m. The spray rate of 280 L ha-1 provided the highest density of droplets per cm2 in the lower third and greater coverage in the middle-third.